Implementasi Standar Akuntansi Keuangan Syariah dalam Mewujudkan Kualitas, Transparansi, dan Akuntabilitas Laporan Keuangan Bank Syariah - Fitri Zahra Berutu; Suci Ramadani; Muhammad Syafril Nasution (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
The development of Islamic banking in Indonesia necessitates a financial reporting system that is of high quality, transparent, and accountable, while remaining compliant with Sharia principles. Sharia Financial Accounting Standards (SAK Syariah) serve as guidelines for the preparation of Islamic bank financial statements to ensure compliance with Sharia principles while also meeting the information needs of stakeholders. This study aims to examine the implementation of SAK Syariah in realizing the quality, transparency, and accountability of Islamic bank financial statements. The research method employed is a qualitative approach using a literature review of regulations, accounting standards, and relevant scientific literature. The findings indicate that the consistent application of SAK Syariah can enhance the quality of financial information, strengthen reporting transparency, and promote accountability in fund management in line with Sharia principles. Nevertheless, challenges in implementation remain, particularly regarding human resource competence and the adjustment of accounting systems. Therefore, improving the competence of Sharia accountants and strengthening supervision are necessary to ensure the optimal implementation of SAK Syariah.